Analysis of a Constant-Volume Diafiltration System with the Ability to Remove Lithium Cations When Using Poly(2-Acrylamido-2-Methyl-1-Propanesulfonic Acid) in Water - Tapiero-Martinez, y (Elsevier Ltd, 2024)
This study describes the synthesis of a poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) and its application for the removal of Li+ in water using a constant-volume diafiltration system. PAMPS with molecular weights exceeding 100 kDa (88 % w/w), polymerisation yields of 97 % and high acidity was obtained. A block experimental design characterized the diafiltration system reporting: Regenerated cellulose (RC) and polyethersulfone (PES) ultrafiltration membranes with a molecular cut-off of 100 kDa can retain up to 1 % Li+ ions through surface charges. But when PAMPS 2000 kDa was used, 89 % of Li+ was removed (%R). Permeate flux (Js) decreases with increasing PAMPS:Li+ ratio, whereas the %R value increases. The filtration process is controlled by diffusion mechanisms according to the Peclet dimensionless number. Using PAMPS 100 kDa with a PAMPS:Li+ ratio (20:1), %R decreases to 76 %, whereas Js increases slightly. PAMPS can be reused 3 consecutive times, maintaining a Li+ cation rejection efficiency of >60 %. Additionally, it was found that the percentage of Li+ rejection capacity exercised with PAMPS is reduced to 60 % when Ca2+, K+, Mg2+ and Na+ cations are present. © 2024 Elsevier Ltd